India and the European Economic Community - Dharma Kumar; Indian Council of World Affairs (Bombay, New York, Asia Pub. House, 1966)
This is a study on the economic and political implications of the European Economic Community on the Indian economy
Issued under the auspices of the Indian Council of World Affairs.
Includes index
osc 09/11/2018
Loans
Keywords: International Economic Relations